Differences in Learning Outcomes Using Discovery Learning and Problem-Based Learning Models on Indonesia's Strategic Position as The World's Maritime Axis - Prihatin, Tri Aprini (Jurnal Penelitian Pendidikan IPA, 2024)
Discovery Learning is a model that invites students to actively learn to discover their knowledge. Meanwhile, Problem-Based Learning is a learning model where students are required to be active in acquiring concepts by solving problems. This research aims to analyze geography learning outcomes using the discovery learning model; determine the results of learning geography using the problem-based learning model; determine differences in geography learning outcomes using discovery learning models and problem-based learning models. The research method used was a quasi-experiment with two classes, namely the experimental class and the control class. Based on the research results, the learning outcomes for class XI IPS 1 were obtained with an average score of 85.8, and the learning outcomes for class learning on geography learning outcomes in class.